Analysis of Students’ Metacognitive Abilities Judging from Gender Differences - M. Pradesta; H Bharata (Pancaran Pendidikan, 2020)
Metacognition is a person's knowledge, awareness and control of the process and the results of his thinking, this study aims to describe the students' metacognitive abilities in solving problems with the Two Variable Equation System (SPLDV). The ability of Metacognition in this study consists of three stages: planning, monitoring, and evaluation. The research is descriptive qualitative. The subjects in this study from class VIII grade students of SMP Negeri 3 Bandar Lampung. Data collection techniques in this study were written tests, observations, interviews, and documentation. The data technique reduction data, presenting data and drawing conclusions. The results of research conducted on male and female students show that there is no difference in using the structure or ability that it already has to solve mathematical problems encountered. However, there are differences in the procedure for carrying out problem-solving. While the steps to plan and look again there are no differences in procedures and concepts.